Does the visual composition of a dish influence the perception of portion size and hedonic preference? - Rowley, J; Spence, C (Elsevier, 2018)
We report two experiments designed to assess how the plating (i.e., visual composition) of a dish influences people's hedonic preferences and their perception of portion size. In Experiment 1 (conducted online; N = 122), we examined whether varying the orientation of the food on the plate (either vertically stacked or horizontally arrayed) would affect people's ratings of liking (of the visual arrangement), willingness-to-pay for the dish, artistic value (how artistic the dish looks), and perceived portion size. Experiment 2 (N = 124) extended this research to a naturalistic dining context, demonstrating the influence of both plating arrangement (horizontal vs. vertical) and centrality (centred vs. offset plating) on the same ratings. In both experiments, the plate of food was rated as constituting a larger portion when the elements were arrayed-horizontally rather than stacked vertically. Additionally, the centrally-plated dessert was rated as a larger portion than the offset version of exactly the same dish. The food was also liked more and the participants/diners were willing to pay more for it when horizontally and/or centrally arranged. These results provide important guidelines for enhancing the visual arrangement of a dish, in order to increase enjoyment, and possibly also nudge consumers toward better food choices.